MINAT BACA PADA PSIKOLOGIS SISWA KELAS 1 SEKOLAH DASAR (SD) 01 KECAMATAN LIMA KAUM KABUPATEN TANAH DATAR - Desnawita Desnawita; Desni Yulinda (IAIN Batusangkar, 2018)
This study aims to describe the reading interest of elementary school students 01 and the factors that influence the reading interest of elementary school 01. This research is a descriptive study with a qualitative approach. The subjects of this study were elementary school students 01. Data collection was carried out using the methods of observation, interviews, and documentation. Interest in reading elementary school students is still low. Based on the results of the study concluded that: reading interest of elementary school students 01 is still low. Judging from the level of student visits to the library that are rarely done. Students prefer to be in class, tell stories with friends, compared to reading books to the library. The low reading interest of students is due to students lacking feelings, attention to books and the benefits of reading, as well as motivation from themselves and from others (the environment). The factors that influence students' mint reading are factors: internal factors (feelings, attention and motivation). The steps taken are by giving motivation, continuous attention to elementary school students 01 and attention to increase reading interest. Factors that influence reading interest from outside consist of the role of teacher, environment, family and facilities. A teacher should use the theory or component of learning strategies as a learning principle so that the learning process can be accepted by students well and more easily. The existence of a library in the school, where the library is a learning resource that is expected to foster interest in reading for students, then it should be managed well, for example a more attractive library design and provide many picture books that can improve the student's motor skills.